Christianity and the roots of morality : philosophical, early Christian and empirical perspectives - Luomanen, Petri, 1961- (Philosophical Studies in Science and Religion, 2017)
What is the role of religion, especially Christianity, in morality, pro-social behavior and altruism? Are there innate human moral capacities in the human mind? When and how did they appear in the history of evolution? What is the real significance of Jesus' teaching in the Sermon on the Mount - does it set up unique moral standards or only crystallize humans' innate moral intuitions? What is the role of religious teachings and religious communities in pro-social behavior? Christianity and the Roots of Morality: Philosophical, Early Christian, and Empirical Perspectives casts light on these questions through interdisciplinary articles by scholars from social sciences, cognitive science, social psychology, sociology of religion, philosophy, systematic theology, comparative religion and biblical studies. Contributors include: Nancy T. Ammerman, István Czachesz, Grace Davie, Jutta Jokiranta, Simo Knuuttila, Kristen Monroe, Mika Ojakangas, Sami Pihlström, Antti Raunio, Heikki Räisänen (✝), Risto Saarinen, Kari Syreeni, Lauri Thurén, Petri Ylikoski.